Development of pickle from Thai pangus (Pangasianodon hypophthalamus) muscle and changes in it’s nutritional composition during storage: Development of pickle from Thai pangus and it’s shelf-life (Journal of the Bangladesh Agricultural University, 2018)
Fish pickle was developed from Thai pangus (Pangasianodon  hypophthalamus) fish muscle by using different types of food additives. Mustard oil and soybean oil were used for preparing fish pickle. Dorsal muscle and whole fish muscle without bone were used as raw material for preparing fish pickle. Changes in nutritional composition, pH, bacteriological and sensory attributes were determined at room temperature (30–35°C) according to standard procedures. At room temperature (30-35°C) fish pickle prepared from dorsal muscle and whole fish muscle using both mustard oil and soybean oil remained in acceptable condition until 12/13 days. Bad smell produced in the pickle after 15th day of storage. Moisture, protein, lipid and pH value decreased but ash content increased with the progress of storage period. In case of soybean oil used pickle deterioration was faster than the pickles prepared using mustard oil. Bacterial load was higher in soybean oil pickle and the pickle prepared from whole fish muscle.J. Bangladesh Agril. Univ. 16(3): 545–552, December 2018